Protective Effects of Platelet-rich plasma for in vitro Fertilization of Rats with Ovarian Failure Induced by Cyclophosphamide - Budak, Özcan; Bostancı, Mehmet Sühha; Toprak, Veysel; Doğanay, Songül; Köse, Osman (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective Premature ovarian insufficiency (POI) contributes significantly to female infertility. Cyclophosphamide (CYC has adverse effects on folliculogenesis. Platelet-rich plasma (PRP) is an autologous product rich in many growth factors. We evaluated the protective effect of PRP on in vitro fertilization in female rats with CYC-induced ovarian damage.Methods Twenty-eight adult female Sprague-Dawley rats were randomly divided into four groups. Group 1 (control-sodium chloride 0.9%; 1 mL/kg, single-dose intraperitoneal [IP] injection); group 2 (CYC), 75 mg/kg, single-dose IP injection and sodium chloride 0.9% (1 mL/kg, single-dose IP injection); group 3 CYC plus PRP, CYC (75 mg/kg, single-dose and PRP (200 μl, single-dose) IP injection); and group 4 (PRP, 200 μl, single-dose IP injection).Results In the comparisons in terms of M1 and M2 oocytes, it was observed that the CYC group presented a significantly lower amount than the control, CYC/PRP, and PRP groups. (for M1, p = 0.000, p = 0.029, p = 0.025; for M2, p = 0.009, p = 0.004, p = 0.000, respectively). The number of fertilized oocytes and two-celled good quality embryos was found to be statistically significant between the CYC and control groups, CYC + PRP and PRP groups (p = 0.009, p = 0.001, p = 0.000 for oocytes, respectively. For embryos; p = 0.016, p = 0.002, p = 0.000).Conclusion Platelet-rich plasma can protect the ovarian function against damage caused by CYC, and, in addition, it improves oocyte count and the development of embryos as a result of oocyte stimulation during the IVF procedure.
Keywords: ovary; premature ovarian insufficiency; cyclophosphamide; in vitro fertilization; platelet-rich plasma